2021
DOI: 10.1007/s00508-021-01886-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of very preterm infants with gastrointestinal tract perforations does not differ compared to controls

Abstract: Summary Purpose To evaluate gastrointestinal tract (GIT) perforations in very low birth weight infants and the effects on neurodevelopmental outcome. Methods Between 2000 and 2017 all cases with GIT perforation were analyzed regarding causes, associated morbidities and neurodevelopmental outcome and compared with matched (gestational age, birth weight, gender, year of birth) by 1:2 controls. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The initial search yielded 1966 results, from which 18 studies were included based on the selection criteria 1 6–9 13 19–31. The study selection process is shown in the PRISMA flow diagram (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 1966 results, from which 18 studies were included based on the selection criteria 1 6–9 13 19–31. The study selection process is shown in the PRISMA flow diagram (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“… 14 19 34 35 However, there is still ongoing debate as different studies have used varying cut-off values. 36 37 38 Therefore, this remains a topic of controversy.…”
Section: Discussionmentioning
confidence: 99%